DEFECTIVE KERNEL1 regulates cellulose synthesis and affects primary cell wall mechanics - Novaković, Lazar; Yakubov, Gleb E.; Ma, Yingxuan; Bacic, Antony; Blank, Kerstin G.; Sampathkumar, Arun; Johnson, Kim L. (Frontiers in Plant Science, 2023)
The cell wall is one of the defining features of plants, controlling cell shape, regulating growth dynamics and hydraulic conductivity, as well as mediating plants interactions with both the external and internal environments. Here we report that a putative mechanosensitive Cys-protease DEFECTIVE KERNEL1 (DEK1) influences the mechanical properties of primary cell walls and regulation of cellulose synthesis. Our results indicate that DEK1 is an important regulator of cellulose synthesis in epidermal tissue of Arabidopsis thaliana cotyledons during early post-embryonic development. DEK1 is involved in regulation of cellulose synthase complexes (CSCs) by modifying their biosynthetic properties, possibly through interactions with various cellulose synthase regulatory proteins. Mechanical properties of the primary cell wall are altered in DEK1 modulated lines with DEK1 affecting both cell wall stiffness and the thickness of the cellulose microfibril bundles in epidermal cell walls of cotyledons.